2021
DOI: 10.15282/jgi.4.2.2021.5573
|View full text |Cite
|
Sign up to set email alerts
|

New Public Management in the Developing Countries: Effects and Implications on Human Resource Management

Abstract: Understanding the linkage between New Public Management (NPM) reforms and Human Resource Management (HRM) are required to be highlighted. A Systematic Literature Review (SLR) used as a research methodology to discuss the implementation of NPM reforms, gaps and challenges of NPM, and the effects and implications of these gaps and challenges on HRM. This paper contributes to the existing literature by offering important lessons and experiences of the implemented NPM reforms, alongside their major gaps and challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…This study followed the need to apply key performance indicators to influence the transformation of local governments at the district level. 37 Similarly, the weakness of the RPSAPHC implementation lay in human resources. 38 Semarang District, Central Java Province, Indonesia, showed that job satisfaction of the health care workers in RPSAPHC was higher in non-RPSA ones, but only in terms of the indicators of coworkers.…”
Section: Discussionmentioning
confidence: 99%
“…This study followed the need to apply key performance indicators to influence the transformation of local governments at the district level. 37 Similarly, the weakness of the RPSAPHC implementation lay in human resources. 38 Semarang District, Central Java Province, Indonesia, showed that job satisfaction of the health care workers in RPSAPHC was higher in non-RPSA ones, but only in terms of the indicators of coworkers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of HR in the 21 st century is well recognized the theoretical underpinnings of the concept have not been fully explored. One of the important areas that need scholarly attention is the institutional context in which HR practices are shaped in an organization in a given context (Mahmoud and Othman, 2021).…”
Section: Npm Reforms Hrm Practices and Institutional Complexitymentioning
confidence: 99%
“…Th e management concept took a long time to evolve as a distinct approach in public intellectual discourses. Only recently researchers have seriously engaged with it and discussed it within a paradigmatic scheme (Mahmoud and Othman, 2021;Poor et al, 2021;Oliveira et al, 2021;Boselie et al, 2021). However, there is no simple way to distinguish between public administration and public management based on the diff erence between administration and management.…”
Section: Literature Reviewmentioning
confidence: 99%